Effect of spraying on coal dust diffusion in a coal mine based on a numerical simulation. (September 2020) - Ma, Qingxin; Nie, Wen; Yang, Shibo; Xu, Changwei; Peng, Huitian; Liu, Zhiqiang; Guo, Cheng; Cai, Xiaojiao
Abstract: Aimed at effectively controlling coal dust pollution in the mining face of a coal mine, this study first conducted a theoretical analysis and then combined a spraying experiment and a numerical simulation to perform an in-depth examination of the atomizing characteristics and dust suppression performance of a coal cutter external spraying device. Based on the experimental spraying results, the optimal nozzle was determined to be a pressure round-mouth nozzle with an X-shaped core. The characteristics of the spray fields from nozzles of different calibers (1.6, 2.0 and 2.4 mm) at different spraying pressures (2, 4, 6 and 8 MPa) were then analyzed. It was found that the droplet concentration in the spray field increased with increasing spraying pressure and nozzle caliber. The droplet diameter was mainly dependent on the spraying pressure and varied more slowly with increased spraying pressure. At a spraying pressure of 8 MPa, the spray field formed could achieve effective dust suppression; specifically, the droplet concentration in the spray field was mostly more than 15 g/m 3, and the droplet size was mainly distributed in the range of 30–100 μm. When using a 2.4 mm caliber nozzle, the dust concentration measured around the coal cutter operator was reduced to 87.21 mg/m 3 under a spraying pressure of 8 MPa, suggesting adequate dust suppression. Graphical abstract: Image 1 Highlights: Innovative improvements to spray equipment. Combining numerical simulation with spray experiments. The influence of spray pressure and nozzle diameter on the fog field is analyzed. Achieved effective dust reduction effect.